Quantum Technologies for Engineering: the materials challenge. (1st March 2022) - Goh, Kuan Eng Johnson; Krivitsky, Leonid A; Polla, Dennis L
Abstract: The materials challenge is often a major hurdle for translating good ideas in science into technologies. This is no different in the arena of quantum technologies which has seen a resurgence of interest in the last decade. This perspective provides a unique insight into the recent collaborative works by research groups in Singapore to surmount key quantum materials and processing bottlenecks that have impeded quantum technologies in the areas of sensing, computing, and communications. We highlight recent important materials related breakthroughs that have made possible novel advancements such as integrated ion traps, light frequency conversion, highly efficient cryogenic contacts to atomically thin quantum devices, and gate defined quantum dots, to name just a few. We also discuss the potential applications and conclude with our perspective on the remaining challenges to be addressed and the prospects enabled by these materials advances for future collaborations and co-developments to advance quantum technologies.